2019
DOI: 10.1002/jcp.28626
|View full text |Cite
|
Sign up to set email alerts
|

Demethoxycurcumin: A naturally occurring curcumin analogue for treating non‐cancerous diseases

Abstract: Turmeric extracts contain three primary compounds, which are commonly referred to as curcuminoids. They are curcumin, demethoxycurcumin (DMC), and bisdemethoxycurcumin. While curcumin has been the most extensively studied of the curcuminoids, it suffers from low overall oral bioavailability due to extremely low absorption as a result of low water solubility and instability at acidic pH, as well as rapid metabolism and clearance from the body. However, DMC, which lacks the methoxy group on the benzene ring of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 119 publications
1
24
0
1
Order By: Relevance
“…Accumulating evidence has shown that DMC is an more effective and stable curcuminoid than CUR or BDMC in cancer treatment of prostate, lung, and brain tumors [24,31,32] and other diseases [33]. In the present study, we observed that DMC exhibited strong oncostatic effects on OSCC cells respectively derived from primary and metastatic sites, including G 2 /M cell-cycle arrest and apoptotic cell death.…”
Section: Discussionsupporting
confidence: 60%
“…Accumulating evidence has shown that DMC is an more effective and stable curcuminoid than CUR or BDMC in cancer treatment of prostate, lung, and brain tumors [24,31,32] and other diseases [33]. In the present study, we observed that DMC exhibited strong oncostatic effects on OSCC cells respectively derived from primary and metastatic sites, including G 2 /M cell-cycle arrest and apoptotic cell death.…”
Section: Discussionsupporting
confidence: 60%
“…Kurkuminoid yang terdapat pada rimpang kunyit memiliki manfaat sebagai antiinflamasi dan antioksidan sehingga dapat dijadikan terapi alternatif pada aterosklerosis. (10,11). Berdasarkan latar belakang tersebut maka peneliti tertarik menganalisis efektivitas rimpang kunyit terhadap penurunan risiko aterosklerosis.…”
Section: Abstrakunclassified
“…Resultantly, DiMC usually displays various pharmacological activities that are mostly maintained and even more improved in contrast to curcumin, which mainly includes anti-inflammatory, antihypertensive, neuroprotective, nephroprotective, and anticancer effects that are primarily attributed to its stability and potent anti-oxidant and free radical scavenger properties ( Karimian et al, 2017 ). Much attention has lately been given to DiMC due to its potency against various cancer cell lines in many cases, such as the ability to serve as an androgen receptor antagonist in human prostate cancer cells in vivo ( Ramkumar et al, 2017 ; Hatamipour et al, 2018 ; Hatamipour et al, 2019 ). Recent research has further revealed the miraculous power of DiMC as an anticancer agent via special actions on various molecular targets, including inactivation of enzymes, regulation of P-glycoprotein activity, inducing apoptosis and promoting autophagy of cancer cells, inhibiting migration, and DNA transcription ( Munigunti et al, 2014 ; Yoon et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%